Mapping of Soil Phospor and Potassium on Paddy Land with 200 Cropping Intensity System in Tanjung Rejo Village Percut Sei Tuan Sub District of Deli Serdang District - Ade Ine Imansari; Razali Razali; Mariani Sembiring (Jurnal Agroekoteknologi, 2018)
This research is aimed to describe soil phosphorus  and pottasium spread in 200 Cropping Intensity paddy field. Location in Tanjung Rejo village Percut Sei Tuan sub district Deli Serdang district, Laboratory of Geographic Information System Agriculture Department of Universitas Sumatera Utara, Laboratory of Soil Chemical and Indonesian Oil Palm Research Institute Laboratory. Soil sampling was done with free grid of storey level semi detail method. Parameters were soil phosphate (HCl 25%) and Soil Pottasium (HCl 25%) and questioner of paddy field. The data was analyzed with interpolation method. The result showed that soil phosphorus spread divided into two criteria’s, respectively medium and high. In the medium criteria was 0,7% of total area and for high criteria was 99,3% of total area with phosphate fertilizer recommendation is SP-36 75 kg / ha / season for medium P2O5 nutrient status and SP-36 50 kg / ha / season for high P2O5 nutrient status. While in soil pottasium spread divided into three criteria’s, the low criteria was 0,4% of total area, for medium criteria 23,7% of total area and for high criteria was 75,9% of total area. with pottasium fertilizer recommendation is KCl 50 kg / ha / season for low K2O nutrient status and no need to fertilized for medium and high K2O nutrient status. Keywords: cropping intensity, fertilization, interpolation, soil phosphorus, soil pottasium.